RECENT PROGRESS IN RESIDUAL STRESS MEASUREMENT TECHNIQUES - Huang, Xianfu; Liu, Zhanwei; Xie, Huimin (Acta mechanica solida Sinica, 2013)
Residual stress measurement is of critical significance to in-service security and the reliability of engineering components, and has been an active area of scientific interest. This paper offers a review of several prominent mechanical release methods for residual stress measurement and recent developments, focusing on the hole-drilling method combined with advanced optical sensing. Some promising trends for mechanical release methods are also analyzed.